USM MY FIRST CHOICE DUE TO INSPIRING BEAUTY AND HIGHLY-RANKED FIELD OF STUDY” - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 23 March 2016 – The Grand Prize winner for ‘Kaki Lima Short Film Competition 2015’ and ‘Yeo’s I Love Malaysia Video Contest 2015’, Teh Chun Yen, 24, chose to enroll for his undergraduate studies at the Universiti Sains Malaysia (USM) School of Communication due to the high ranking of the USM school in Malaysia.